FRI0202 Safe and Effective Tocilizumab Therapy in Elderly Patients with Rheumatoid Arthritis. (15th July 2016) - Specker, C.; Kaufmann, J.; Kellner, H.; Kästner, P.; Volberg, C.; Braunewell, V.; Aringer, A.; Sieburg, M.; Meier, L.; Hofmann, M.W.; Flacke, J.-P.; Tony, H.-P.; et al.
Abstract : Background: The single-arm non-interventional study ICHIBAN was set up to evaluate the effectiveness and safety of intravenously administered Tocilizumab (TCZ IV) in patients (pts) with moderate to severe rheumatoid arthritis (RA) in Germany. Clinical data were collected during routine medical consultations including concomitant therapies, co-morbidities, therapeutic responses and adverse events. Objectives: This interim analysis assessed the effectiveness and safety of long-term TCZ IV treatment with respect to patients' age. Methods: Since February 2010 ∼250 German rheumatology study centres collected these prospective data. Pts were observed for a maximum period of 2 years (104 weeks). The present interim analysis included pts with complete baseline (BL) data before 03rd December 2015 (group total; n=2999). 902 pts have completed the maximal 104 week observation period (group W104). Subgroups according to age have been defined as <50 years, 50–65 years, >65 years. Results: At BL the age distribution showed the following proportions: <50 years 28.9%, 50–65 years 48.6%, and >65 years 22.5%. The mean TCZ IV treatment duration was 1.7, 1.8, and 1.7 years, respectively, for the three age groups. In comparison to younger pts, the elderly (>65 years) showed longer disease duration, higher inflammatory parameters, higher disease activity, and higher co-morbidity rates at BL. Nevertheless, TCZ IV showed comparable effectiveness in all age groups. At last visit, DAS28-BSG remission (<2.6) was reached by 55.2%, 51.6%, and 48.8% of pts aged <50, 50–65, and >65 years, respectively. The mean reduction from BL in DAS28-BSG was 2.6, 2.7, and 2.8, respectively. Regarding co-medication, the mean glucocorticosteroid (GC) dose was reduced from 7.1 (BL) to 4.6 mg/d (last visit) and was similar in all subgroups. About 12% of pts stopped GC therapy completely, again similar in all subgroups. At baseline, the rate of TCZ monotherapy (without concomitant sDMARD) was highest in the elderly (53.2%) while combination therapy is more common in younger pts (47.1%). The rate of sDMARD discontinuation while receiving TCZ is comparable in all subgroups (11.5%, 12.1%, 12.3%). Despite slightly higher incidence rates of adverse events (AE) and serious adverse events (SAE) for the elderly, the rates of infections, serious infections and TCZ discontinuation rates due to an AE did not increase with age (Table 1 ). Gastrointestinal perforation was rarely observed. Conclusions: TCZ IV treatment resulted in improvement of disease activity and reduction in concomitant GC dosing were observed. Despite higher disease burden at baseline, elderly RA patients (>65 years) benefited to the same extent as younger patients, without increased risk of infections. Considering natural age related risks, the low infection and gastrointestinal perforation rates of elderly patients seem to be attributable to the steroid sparing effect of TCZ therapy. Safety concerns should be no reason to argue against anti-IL-6 therapy in elderly patients. Disclosure of Interest: C. Specker Consultant for: Roche, Chugai, Speakers bureau: Roche, Chugai, J. Kaufmann: None declared, H. Kellner: None declared, P. Kästner: None declared, C. Volberg: None declared, V. Braunewell: None declared, A. Aringer Consultant for: Roche, Chugai, Speakers bureau: Roche, Chugai, M. Sieburg: None declared, L. Meier: None declared, M. Hofmann Employee of: Chugai Pharma Europe Ltd., J.-P. Flacke Employee of: Roche Pharma AG, H.-P. Tony Grant/research support from: Roche Pharma AG, Consultant for: Abbvie, BMS, Chugai, Janssen, Lilly, Novartis, Roche, UCB, Speakers bureau: Abbvie, BMS, Chugai, Janssen, Lilly, Novartis, Roche, UCB, G. Fliedner Consultant for: Chugai Pharma Europe Ltd., Paid instructor for: Chugai Pharma Europe Ltd.